The Soybean Trap: Challenges and Risks for Brazilian Producers - Bicudo Da Silva, Ramon Felipe; Batistella, Mateus; Moran, Emilio; Celidonio, Otávio Lemos De Melo; Millington, James D. A. (Frontiers in Sustainable Food Systems, 2020)
Since the 1970s, Brazilian soybean production has grown rapidly, driven by increasing national and international demand and rising prices. Consequently, soybean production has come to be perceived as an attractive opportunity, with the number of farms producing soybean across the country reaching around 240,000 in 2017. However, producers can become trapped by dependencies on moneylenders, traders and input supply companies, facing so-called ’agricultural treadmills’. In this study we undertook interviews with individual soybean producers and representatives of trader companies, producers’ associations, the processing industry, government and civil society, and used these data to analyze rural production operations related to the soybean supply chain and to interpret how agricultural treadmills persist in this sector. Based on literature review and fieldwork interviews, we found that producers have been able to add value to their products, but some strategies they use to cope with production costs lead them into high-risk situations. Our findings show that, sectoral (e.g., producers’ associations) and collective actions (e.g., farmers’ buying groups) are a useful strategy for producers to gain influence and bargaining power against transnational companies and input suppliers compared to acting as an individual within the soybean supply chain. Producers were emphatic that the current soybean business is now much more than just farming activities, and that education and training are highly valuable and important strategies to keep producers in the soybean business and out of traps. These findings are important given the neoliberal context in which individual producers find themselves and which presents challenges that alone they can do little to change. Policies that enable individual producers to make environmentally- and financially-sound agricultural decisions are vital to ensure a sustainable soybean system that does not trap producers in endless cycles of debt and investment.